Design of a polarization insensitive SPR biosensor for malaria and cancer detection - Hasan Masud Khan; Shah Laheen Mashahad; Md. Asiful Islam; M. Shah Alam (Sensing and Bio-Sensing Research)
A polarization-insensitive photonic crystal fiber (PI-PCF) based surface plasmon resonance (SPR) biosensor is designed and analyzed for multianalyte detection. In this work, a simple symmetrical structure is designed using only eight circular-shaped air holes, which makes it not only polarization-insensitive (PI) but also fabrication friendly and reliable. Tantalum pentaoxide (Ta2O5) is used with gold (Au) as the plasmonic material to increase SPR excitation, solve adhesion issues, and minimize the reliance on gold. The analytes are placed on the periphery to facilitate the operation of the sensor. The numerical investigations are conducted using the full-vector finite element method (FEM) based COMSOL Multiphysics software to obtain modal solutions (effective refractive index, field distribution) of core and plasmonic modes of the sensor structure. By optimizing its structural parameters, the sensor has demonstrated a maximum wavelength sensitivity (WS) of 65,000 nm/RIU, amplitude sensitivity (AS) of 3709.66 RIU−1, and figure of merit (FOM) of 1160.71 RIU−1, sensor resolution (SR) of 1.53 × 10−6 RIU, for both x and y-polarizations to detect unknown analyte refractive indices (RIs) from 1.28 to 1.42. Furthermore, the sensor can be used to detect different phases of malaria disease, including ring, schizont and trophozoite phases; it shows the WS of 10,000 nm/RIU for the ring phase and the AS of 2042.77 RIU−1 for the trophozoite phase. Moreover, it can detect six distinct varieties of cancer cells, with WS of 7857.14 nm/RIU for breast (MCF-7) and AS of 5281.01 RIU−1 for cervical (HeLa). The sensor's sensitivity is not significantly affected by air hole dimensions, ensuring high structural tolerance. Its exceptional performance and favorable manufacturing likelihood make it a valuable candidate for biological, biomedical, and biochemical analyte sensing application.